Reduction of aggressive and violent behavior toward behavioral health unit staff and other patients: a best practice implementation project. Issue 2 (4th June 2021) - Badeaux, Jennifer E.; Triche, Tyrus; Bennett, Marsha J.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: The current project aimed to implement evidence-based recommendations for the management of inpatient aggressive and violent behaviors in four behavioral health units (BHUs) in a mental healthcare area within an academic medical center. Introduction: Patient violence against healthcare workers is a global concern, particularly in mental health care. All employees who work in inpatient psychiatric environments are at higher risk for targeted violence than are other healthcare workers. For healthcare organizations and staff, violent episodes involving patients can bring about medical expenses, potential legal expenditure, sick leave and a high turnover rate. The hospital at which this project was implemented had been experiencing a steady increase in violence and aggressive behavior. Methods: The project used the Joanna Briggs Institute Practical Application of Clinical Evidence System and Getting Research into Practice audit tool for promoting practice change in four BHUs. A baseline retrospective audit of 10 electronic health records from four BHUs assessed compliance with best practice regarding violent episodes. The Getting Research into Practice tool was used to identify barriers and develop an evidence-based educational strategy for 70 BHU staff aimed to improve compliance with best practice for managing aggression and violence. Staff education compliance was assessed via hospital education department records. A pre and postimplementation staff satisfaction survey assessed perceptions about education, confidence and unit safety. Results: The baseline audit indicated that one of the three criteria had 0% compliance. Following implementation of an educational strategy using mock codes for BHU staff, there was 96% improvement in compliance for the BHU staff education audit criterion. Staff de-escalated patients in 83% of the episodes postimplementation. There was a slight decrease (9.1%) in the rate of violence across all four inpatient BHUs. Staff satisfaction survey findings did not show a statistically significant difference. Conclusion: Enhanced evidence-based education and mock codes resulted in BHU staff competence and confidence in managing aggressive and/or violent patients. Early signs of a decrease in the violence rate and improvement in the efficient use of de-escalation will be sustained with on-going yearly education, quarterly mock codes and future audits. This project was limited by its small size and short timeframe (21 weeks), making results not generalizable.